The Influence Of Morinda Citrifolia Fruit As Liquid Organic Fertilizer (Poc) For The Growth And Yield Of Shallots (Allium Ascalonicum L.) - fadlika mawali; Selvie Tumbelaka; Tommy D. Sondakh; Ronny Nangoi (Sam Ratulangi University, 2023)
Liquid organic fertilizer is organic fertilizer in liquid form and is generally an organic substance dissolved in a solvent such as water. Organic fertilizers are not only in solid form in liquid form like inorganic fertilizers. This study aims to study the effect of noni liquid organic fertilizer on the growth and yield of shallot plants and to determine the best dosage of noni liquid organic fertilizer on the growth and yield of shallot plants. This study used a completely randomized design (CRD). In this experiment there were 4 treatments, namely P0 : 0% POC (without treatment), P1 : 10% liquid fertilizer made from noni, P2 : 20% liquid fertilizer made from noni, P3 : 30% liquid fertilizer made from noni. Each treatment was repeated 4 times to obtain 16 experimental plants. Parameters observed were plant height, number of tillers, number of leaves, fresh weight and dry weight. Noni fruit as POC did not significantly affect the growth and yield of shallots. The best concentration that can be used for shallots is 20% POC of noni fruit. Keywords. Organic fertilizer, POC, noni fruit, red onion Abstrak Pupuk organik cair adalah pupuk organik yang berbentuk cair dan umumnya merupakan bahan organik yang dilarutkan dalam suatu pelarut seperti air. Pupuk organik tidak hanya berbentuk padat dalam bentuk cair seperti halnya pupuk anorganik. Penelitian ini bertujuan untuk mempelajari pengaruh pupuk organik cair mengkudu terhadap pertumbuhan dan hasil tanaman bawang merah serta menentukan dosis pupuk organik cair mengkudu yang terbaik terhadap pertumbuhan dan hasil tanaman bawang merah. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL). Pada percobaan ini terdapat 4 perlakuan yaitu P0 : 0% POC (tanpa perlakuan), P1 : 10% pupuk cair berbahan mengkudu, P2 : 20% pupuk cair berbahan mengkudu, P3 : 30% pupuk cair berbahan mengkudu. Setiap perlakuan diulang sebanyak 4 kali sehingga diperoleh 16 tanaman percobaan. Parameter yang diamati adalah tinggi tanaman, jumlah anakan, jumlah daun, berat segar dan berat kering. Buah mengkudu sebagai POC tidak berpengaruh nyata terhadap pertumbuhan dan hasil bawang merah. Konsentrasi terbaik yang dapat digunakan untuk bawang merah adalah 20% POC buah mengkudu. Kata kunci. Pupuk organik, POC, buah mengkudu, bawang merah